2005
DOI: 10.1111/j.1742-1241.2005.00546.x
|View full text |Cite
|
Sign up to set email alerts
|

Biological characteristics of breast cancer at the primary tumour and the involved lymph nodes

Abstract: Diminished oestrogen receptor (ER) expression in the involved axillary lymph nodes (ALN) in breast cancer compared with the primary tumour has been reported in previous studies. We have assessed a wider spectrum of tumour markers (ER, progesterone receptor (PgR), p53, Ki-67 and HER-2/neu) and compared extent and staining intensities at the primary tumour and the involved ALN on specimens of 22 cases with invasive ductal breast cancer. At the involved ALN, both the quantity of positive staining cells and the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 22 publications
(24 reference statements)
1
15
0
Order By: Relevance
“…In the present study, our results showed the Ki-67 expression was not related to the number of metastatic lymph nodes, in agreement with a previous report [31]. In addition, Ki-67 expression in axillary lymph nodes is significantly higher in lymph nodes than that in primary cancer in some cases [31], [32], which may be explained that cancer cells with potent proliferative capability are more likely to metastasize from the primary cancer to the axillary lymph nodes. Analysis of patients with divergent Ki-67 expression in primary versus metastatic lesions suggests that the prognostic value of Ki-67 (>10%) on survival was greater in the tumors located in the nodes than that in the primary lesion [24], [31].…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, our results showed the Ki-67 expression was not related to the number of metastatic lymph nodes, in agreement with a previous report [31]. In addition, Ki-67 expression in axillary lymph nodes is significantly higher in lymph nodes than that in primary cancer in some cases [31], [32], which may be explained that cancer cells with potent proliferative capability are more likely to metastasize from the primary cancer to the axillary lymph nodes. Analysis of patients with divergent Ki-67 expression in primary versus metastatic lesions suggests that the prognostic value of Ki-67 (>10%) on survival was greater in the tumors located in the nodes than that in the primary lesion [24], [31].…”
Section: Discussionsupporting
confidence: 92%
“…The expression patterns of hormone receptors and Ki67 may especially show differences in the tumor cells at the lymph nodes and the primary lesion, probably due to tumor cell heterogeneity in parallel to increased tumor burden [77] . Although research results indicate that these multigene molecular assays can reclassify some breast cancer patients who are ranked as high risk using the traditional classification systems into low risk (i.e., reducing the number of patients who might unnecessarily undergo chemotherapy) and vice versa, available data are insufficient to challenge classical classification systems and to justify withholding chemotherapy for high risk patients if classified as low risk using multigene assays.…”
Section: Breast Cancer Indexmentioning
confidence: 99%
“…Dikicioglu et al [5] concluded that lymphatic metastasis presented a significative trend to reduce the expression of oestrogen and progesterone receptors and an increase in the expression of Ki-67, but there were no differences in the expression of HER-2 and p53.…”
Section: Discussionmentioning
confidence: 97%